A perspective combination of quantum dots and silica nanoparticles for bioconjugation with antibodies used in immunosensors for detection of human alpha-fetoprotein - Kovářová, Aneta; Drbohlavová, Jana; Bílková, Zuzana; Korecká, Lucie (BEST Servis, 2017)
The combination of quantum dots (QDs) with silica nanoparticles (SiNPs) as promising signal-generating label of antibodies used in electrochemical immunosensor is described. QDs-modified silica nanoparticles were conjugated with specific antibodies targeted to alpha-fetoprotein (AFP) to a creation of anti-AFP-SiNPs-QDs IgG conjugate for subsequent exploitation in quantum dot-linked immunosorbent assay (QLISA). Square wave anodic stripping voltammetry (SWASV) on mercury or bismuth film modified carbon screen-printed three-electrode sensors was used as a detection method. Insertion of nanoparticles to this system led to the achievement of higher current responses compare to results obtained with QDs only. Therefore, the sensitivity of complete immunoassay could be significantly improved.
Perspektivní kombinace kvantových teček a silika nanočástic pro značení protilátek v imunosenzorech při detekci alfa-fetoproteinu
Keywords: Quantum dots; Silica nanoparticles; Antibody label; Electrochemical immunosensors; SWASV; Kvantové tečky; Silika nanočástice; Značení protilátek; Elektrochemické imunosenzory; SWASV